LEGAL FOUNDATIONS FOR THE DEVELOPMENT OF A CIRCULAR BIOECONOMY: UKRAINIAN AND EUROPEAN DIMENSIONS - Olena Hafurova; Volodymyr Yermolenko; Tamara Novak (Baltic Journal of Economic Studies)
The relevance of researching the legal foundations of the circular bioeconomy is determined by a number of factors. Firstly, there is an objective need today to find an effective alternative to the linear economic model, which is based on intensive extraction and use of resources, followed by waste disposal, and which has a negative impact on the environment and depletes natural resources. The authors consider such an alternative to be a circular economy based on the principles of closed-loop technologies and rational resource and energy consumption. Secondly, given the potential of Ukraine's agricultural sector and the current realities of its functioning, the formation of a circular bioeconomy model, in which agricultural production should play a key role, is promising for Ukraine. Thirdly, it is time to develop a legal framework for regulating relations in the field of circular economy and circular bioeconomy. This process for Ukraine should be based on international, primarily European, experience, which in turn requires research into the relevant provisions of European Union legislation. It is also necessary to develop a unified conceptual and categorical framework. Conducting scientific research on these issues is the purpose of this article. Its achievement was facilitated by the use of such methods of scientific cognition as: philosophical (dialectical) method, general scientific (formal logical and analytical methods) and special scientific (formal legal and comparative legal) methods. As a result, the authors formulated their definition of the concept of "circular bioeconomy" as "an economic model aimed at creating conditions for ensuring food security in the country through the functioning of waste-free (including) agricultural production based on the use of mainly bioenergy resources, which reduces the negative impact on the environment". The paper argues for the circular bioeconomy principles to be used in rebuilding rural areas that got hit by the war. It shows that the circular bioeconomy isn't really covered by Ukrainian laws at the moment. The present study aims to characterise the principles of state policy and existing measures of state support for bioenergy as a direction of the circular bioeconomy. The necessity of the implementation of a state target programme for bioenergy in Ukraine has been demonstrated. Particular emphasis is placed on the analysis of European Union legislation regulating circular bioeconomy relations, and its positive features that could be taken into account by Ukrainian lawmakers are identified. The generalisations obtained can serve as a basis for formulating the content of regulatory and legal acts in the field of circular bioeconomy and bioenergy, as well as material for promising scientific research on this issue.